Reporting Obligations for Attorneys in Money Laundering Cases: Attorney-Client Privilege Under Pressure? - Hofmann, Robin; Lustenberger, Livio (German law journal, 2023)
With the publication of the Panama Papers in 2016, law firms and attorneys came under the spotlight of international anti-money laundering efforts. It became clear that attorneys, protected by the attorney-client privilege, play a significant role in concealing the origin of illicit funds and the constructing of offshore company-schemes. The public outcry prompted legislators to hold these facilitators accountable and to prevent money-laundering activities by imposing reporting obligation on them, whenever there is the suspicion of a client being involved in illicit activities. Unsurprisingly, attorney and professional associations voiced considerable opposition to these legislative efforts claiming an erosion of the attorney client privilege and nothing less than an attack on the rule of law. This article examines the attorney-client privilege from a historical, empirical, and constitutional perspective. A brief analysis of the legal frameworks in Germany and Switzerland exemplifies how reporting obligations affect legal practice and what challenges exist for attorneys. Both countries are considered global hubs for money laundering activities. The legal concepts of holding attorneys accountable in the neighboring countries differ in some respects. In conclusion, it shows that the legal professions successfully managed to widely avoid a ‘responsibilization’.